Mechanistic analysis of a synthetic inhibitor of the Pseudomonas aeruginosa LasI quorum-sensing signal synthase - Lidor, O. (Sci Rep, 2015)
Pseudomonas aeruginosa is an opportunistic Gram-negative pathogen responsible for many human infections. LasI is an acyl-homoserine lactone synthase that produces a quorum-sensing (QS) signal that positively regulates numerous P. aeruginosa virulence determinants. The inhibition of the LasI protein is therefore an attractive drug target. In this study, a novel in silico to in vitro complementation was applied to screen thiazolidinedione-type compounds for their ability to inhibit biofilm formation at concentrations not affecting bacterial growth. The compound (z)-5-octylidenethiazolidine-2, 4-dione (TZD-C8) was a strong inhibitor of biofilm formation and chosen for further study. Structural exploration of in silico docking predicted that the compound had high affinity for the LasI activity pocket. The TZD-C8 compound was also predicted to create hydrogen bonds with residues Arg30 and Ile107. Site-directed mutagenesis (SDM) of these two sites demonstrated that TZD-C8 inhibition was abolished in the lasI double mutant PAO-R30D, I107S. In addition, in vitro swarming motility and quorum sensing signal production were affected by TZD-C 8, confirming this compound alters the cell to cell signalling circuitry. Overall, this novel inhibitor of P. aeruginosa quorum sensing shows great promise and validates our mechanistic approach to discovering inhibitors of LuxI-type acyl-homoserine lactone synthases.